A inclusão de estudantes com transtorno do espectro autista em classes regulares de uma escola da rede pública - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present work aims to identify possible inclusion strategies that contribute to the teaching-learning process of students with autism spectrum disorder (ASD) in the regular classroom of a municipal school in Itaqui - RS. In an inclusive school, it is important that the diagnosis (or the search for a diagnosis) of ASD is shared with all employees, in particular with teachers so that they can develop adjustments and adaptations, always trying to encourage the student to carry out activities. This is a great challenge and an opportune moment in which teachers can seek help through training courses and additional training. As a methodological procedure, a case study was carried out in a public school - municipal - in the city of Itaqui - RS through interviews to investigate the main difficulties faced by professionals involved in the teaching-learning process of students with ASD and if (and in what way) the family of these students is present in the school environment. As a result, we present the data collected in the interviews as well as a brief discussion (based on legislation, on scientific literature related to the subject and on the answers to the questions made) about how the inclusion of students with ASD is carried out in this specific context. It was possible to conclude that the target school of our study follows the current legislation and is considered inclusive by the sample of the school community that participated in this research and also by the author of this work (in his analysis of the obtained reports).
Keywords: Inclusão; Educação; Ambiente escolar; Autismo; Inclusion; Education; School environment; Autism; CNPQ::CIENCIAS EXATAS E DA TERRA